Identification of a novel SALL4 variant associated with unilateral renal agenesis and right renal pelvis duplication by prenatal exome sequencing: a case report - Zhao, Tingting; Liu, Jie (Frontiers in Pediatrics, 2025)
Congenital renal anomalies are one of the leading causes of perinatal and neonatal mortality in children. Here, we present a case of a 17-week-6-day pregnant patient, in whom prenatal ultrasound confirmed the fetal right duplex kidney and left renal agenesis, leading to termination of pregnancy at the patient's request. Whole-exome sequencing were conducted on the fetus and its parents to identify the cause of the fetal ultrasound abnormalities, followed by validation with Sanger sequencing and CMA/SNP-Array. Bioinformatics analysis assessed the pathogenicity of the mutation site using SIFT, PolyPhen-2, and Mutation Taster. A de novo heterozygous mutation c.486_487del(p.P163Hfs*17) was identified in exon 2 of the SALL4 gene, with neither parent carrying the mutation. The bioinformatics analysis results all support that the mutation is pathogenic. This frameshift mutation results in a complete alteration of the base sequence from the mutation site, leading to an abnormal amino acid translation and subsequent manifestation of the disease phenotype. Additionally, a maternally inherited 698.8 Kb deletion in the 2q13 region (seq[GRCh37] 2q13(110697011_111395836)x1) was detected in the fetus. Our study identified a novel de novo frameshift mutation in exon 2 of the SALL4 gene. This mutation is associated with unilateral renal agenesis and duplication of renal pelvis, providing valuable insights for genetic counseling and prenatal diagnosis of SALL4-related disorders.